2020
DOI: 10.1063/5.0022191
|View full text |Cite
|
Sign up to set email alerts
|

Sputter-deposited low-stress boron carbide films

Abstract: Significant challenges have been faced in the manufacturing of low-stress B4C films. Here, we demonstrate a set of process parameters for direct-current magnetron sputter deposition of smooth, high-purity, amorphous B4C films with near-zero total residual stress and with thicknesses up to 10 μm. Films are characterized by a combination of high-energy ion scattering, x-ray diffraction, electron microscopy, and stress measurements based on substrate curvature. In order to facilitate the process transfer to other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Even so, we do observe similar densities of the films grown in experiment #5 through #8. In the work by Engwall et al 16 , they describe the density decrease in boron carbide film deposited under a high working gas pressure and a low working gas pressure by atomic shadowing of boron and carbon atoms. This relates to the elastic scattering of the sputtered atoms with the argon atoms in the chamber atmosphere.…”
Section: Single Layer Boron Carbidementioning
confidence: 99%
“…Even so, we do observe similar densities of the films grown in experiment #5 through #8. In the work by Engwall et al 16 , they describe the density decrease in boron carbide film deposited under a high working gas pressure and a low working gas pressure by atomic shadowing of boron and carbon atoms. This relates to the elastic scattering of the sputtered atoms with the argon atoms in the chamber atmosphere.…”
Section: Single Layer Boron Carbidementioning
confidence: 99%
“…However, the film density will also change due to the unstable preparation process. It was also found that the density of B 4 C films varied in different experiments [ 26 , 27 , 28 , 29 , 30 ]. The influence of the density change under irradiation with high energy X-rays is unclear, especially for the damage threshold.…”
Section: Introductionmentioning
confidence: 99%